2017
DOI: 10.1002/etc.3855
|View full text |Cite
|
Sign up to set email alerts
|

Impaired swim bladder inflation in early life stage fathead minnows exposed to a deiodinase inhibitor, iopanoic acid

Abstract: Inflation of the posterior and/or anterior swim bladder is a process previously demonstrated to be regulated by thyroid hormones. We investigated whether inhibition of deiodinases, which convert thyroxine (T4) to the more biologically active form, 3,5,3'-triiodothyronine (T3), would impact swim bladder inflation. Two experiments were conducted using a model deiodinase inhibitor, iopanoic acid (IOP). First, fathead minnow embryos were exposed to 0.6, 1.9, or 6.0 mg/L or control water until 6 d postfertilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 45 publications
3
29
0
Order By: Relevance
“…2-7). We previously showed that disruption of TH levels during embryonic development interferes with normal inflation of the posterior swim bladder chamber after combined knockdown of dio1 and dio2 or knockdown of dio3b in zebrafish (Bagci et al, 2015), and exposure to a model deiodinase inhibitor in fathead minnow (Cavallin et al, 2017). In both fathead minnow and zebrafish, we observed a peak in the transcript levels of dio1 and in zebrafish we additionally observed a peak of dio2 and dio3b mRNA levels at the time of posterior swim bladder chamber inflation (Psb in Fig.…”
Section: Hpt Axis Functionality During Embryo-larval Transitionmentioning
confidence: 99%
“…2-7). We previously showed that disruption of TH levels during embryonic development interferes with normal inflation of the posterior swim bladder chamber after combined knockdown of dio1 and dio2 or knockdown of dio3b in zebrafish (Bagci et al, 2015), and exposure to a model deiodinase inhibitor in fathead minnow (Cavallin et al, 2017). In both fathead minnow and zebrafish, we observed a peak in the transcript levels of dio1 and in zebrafish we additionally observed a peak of dio2 and dio3b mRNA levels at the time of posterior swim bladder chamber inflation (Psb in Fig.…”
Section: Hpt Axis Functionality During Embryo-larval Transitionmentioning
confidence: 99%
“…Dio1 could therefore also be important during embryogenesis and metamorphosis of fish, when the demand for THs is high (Orozco et al, 2012). In fathead minnows exposed to IOP, a strong DIO1 and DIO2 inhibitor according to our data, during the period of anterior chamber inflation, dio2 mRNA levels increased, possibly as a compensatory response, while dio1 mRNA levels did not (Cavallin et al, 2017). Therefore, it seems plausible that Dio2 inhibition is more important for causing impaired posterior and anterior chamber inflation.…”
Section: Linking In Chemico Data To In Vivo Datamentioning
confidence: 50%
“…In a follow-up study, we also plan to assess whether these in chemico assays can be used to predict endpoints in a 30 days fish early-life stage (FELS) chronic toxicity test, as the FELS test (OECD TG 210; OECD, 2013b) is one of the primary assays used to assess the chronic aquatic toxicity of chemicals in fish. Disruption of thyroid function has already been reported to affect anterior swim bladder chamber inflation (Cavallin et al, 2017;Godfrey et al, 2017;Nelson et al, 2016;Stinckens et al, 2016), a chronic adverse outcome which cannot be observed in acute ZFET experiments.…”
Section: In Vivo Acute Zebrafish Embryo Toxicity Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the molecular mechanisms of thyroid organogenesis and the role of TR signaling during embryogenesis are well documented for zebrafish and seem to be highly conserved between zebrafish and mammalian models [26,31]. (Neuro)developmental processes that are, at least partially, regulated by THs include eye development, swim bladder inflation and fin formation during early embryonic development and the metamorphosis from the larval to juvenile stage [33][34][35][36][37]. Exposure to THDs has been shown to affect these important developmental processes, which makes them promising candidates for thyroid-related endpoints in THD fish testing assays.…”
Section: Conceptmentioning
confidence: 99%